Suplementasi Calcitriol Meningkatkan Retensi Kalsium Tikus Ovariektomi - Hartiningsih Hartiningsih; Devita Anggraeni; Dhirgo Aji (Jurnal Sain Veteriner, 2011)
The objective of the research was to study calcitriol supplementattion for 1,5 months in ovariectomized rats on calcium retention.